Integrated Analysis of Olive Mill Wastewaters: Physicochemical Profiling, Antifungal Activity, and Biocontrol Potential Against Botryosphaeriaceae - Elena Petrović; Karolina Vrandečić; Alen Albreht; Igor Gruntar; Nikola Major; Jasenka Ćosić; Zoran Užila; Smiljana Goreta Ban; Sara Godena (Horticulturae)
The disposal of olive mill wastewater (OMWW) poses significant environmental challenges due to its high content of phytotoxic and pollutant compounds. This study aims to explore the chemical composition of OMWW derived from various olive varieties (Buža, Buža puntoža, Istarska bjelica, Leccino, and Rosinjola) and assess its antifungal potential against phytopathogenic fungi from the Botryosphaeriaceae family. OMWW samples were analyzed for their physicochemical properties, phenolic composition via LC-MS/MS, and antifungal activity against Botryosphaeria dothidea (Moug. ex Fr.) Ces. & De Not., Diplodia mutila (Fr.) Fr., D. seriata De Not., Dothiorella iberica A.J.L. Phillips, J. Luque & A. Alves, Do. sarmentorum (Fr.) A.J.L. Phillips, Alves & Luque, and Neofusicoccum parvum (Pennycook & Samuels) Crous, Slippers & A.J.L. Phillips. Antifungal efficacy was tested at varying concentrations, alongside the phenolic compounds hydroxytyrosol and vanillic acid. Antifungal activity varied across fungal species and OMWW concentrations. Lower OMWW concentrations inhibited mycelial growth in some pathogens, while higher concentrations often had a stimulatory effect. Among the OMWW treatments, Leccino and Buža showed the most significant antifungal activity against species from the Botryosphaeriaceae family. The results demonstrated significant variability in OMWW composition, with Istarska bjelica exhibiting the highest concentrations of phenolic compounds, sugars, dry matter, and carbon and nitrogen content. The results also highlight the impact of acidification on the phenolic profile of OMWW. Treatment with HCl significantly altered the concentration of individual phenolic compounds, either enhancing their release or contributing to their degradation. Among the two compounds, vanillic acid showed greater efficacy than hydroxytyrosol. In addition, microorganisms isolated from OMWW, including Bacillus velezensis Ruiz-Garcia et al., Rhodotorula mucilaginosa (A. Jörg.) F.C. Harrison, Nakazawaea molendiniolei (N. Cadez, B. Turchetti & G. Peter) C. P. Kurtzman & C. J. Robnett, and Penicillium crustosum Thom, demonstrated antagonistic potential against fungal pathogens, with B. velezensis showing the strongest inhibitory effect. The greatest antagonistic effect against fungi was observed with the species Do. Iberica. The findings highlight the potential of OMWW as a sustainable alternative to chemical fungicides, simultaneously contributing to the management of waste and protection of plants through circular economy principles.